Characterization of photo-intermediates in the photo-reaction pathways of a bacteriorhodopsin Y185F mutant using in situ photo-irradiation solid-state NMR spectroscopy1. Issue 9 (26th September 2015) - Oshima, Kyosuke; Shigeta, Arisu; Makino, Yoshiteru; Kawamura, Izuru; Okitsu, Takashi; Wada, Akimori; Tuzi, Satoru; Iwasa, Tatsuo; Naito, Akira
<x xml:space="preserve">Abstract</x> Photo-reaction pathways of a Y185F-bR mutant and, CS*- and O-intermediates were examined using in situ photo-irradiation solid-state 13C NMR spectroscopy.